2007
DOI: 10.1159/000103798
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia in Hemodialysis Patients: The Possible Role of Des-Acyl Ghrelin

Abstract: Background: Anorexia is frequently found in end-stage renal disease and is a reliable predictor of morbidity and mortality in hemodialysis (HD) patients. The pathogenesis of anorexia is complex and the appetite-modulating hormone ghrelin could be involved. Two forms of circulating ghrelin have been described: acylated ghrelin (<10% of circulating ghrelin) which promotes food intake, and des-acyl ghrelin which induces a negative energy balance. The aim of this cross-sectional study is to clarify whether anorexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 67 publications
1
39
0
3
Order By: Relevance
“…We did demonstrate that DG increased with decreasing eGFR, as described by others (16,37). DG has been reported to be the "inactive" degradation product of AG but recent studies suggest that DG may itself have pleiotropic biologic activities, including opposing actions to AG (38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 86%
“…We did demonstrate that DG increased with decreasing eGFR, as described by others (16,37). DG has been reported to be the "inactive" degradation product of AG but recent studies suggest that DG may itself have pleiotropic biologic activities, including opposing actions to AG (38)(39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 86%
“…It has been previously shown that HD present higher levels of des acyl-ghrelin compared to healthy individuals. 6 However, this pilot study may contribute with data showed about acyl-ghrelin and obestatin in response to acute exercise and further studies with a whole spectrum of the ghrelin products may be necessary.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 Altered plasma levels of hormones related to appetite (ghrelin, acylghrelin and obestatin) have been reported in CKD patients, and although there are many contradictory published data, CKD patients usually present low acyl-ghrelin and high obestatin levels. [4][5][6] Strategies have been proposed to reverse the anorexia and, physical activity may be beneficial to increase appetite in CKD patients. 7 Studies about the effects of exercise on acyl-ghrelin and obestatin in CKD patients are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Both peripheral and central injection of des-acyl ghrelin before acyl ghrelin consistently blocked the stimulatory effects on food intake induced by acyl ghrelin alone in the goldfish (Carassius auratus) (Matsuda et al, 2006), indicating that the interactions between acyl ghrelin and des-acyl ghrelin could be observed across species. Promisingly, des-acyl ghrelin was demonstrated to be involved in the regulation of human appetite (Muscaritoli et al, 2007). Moreover, a decrease in body weight and fat pad mass weight accompanied moderately decreased linear growth in des-acyl ghrelin-overexpressing mice has been shown by two independent studies Asakawa et al, 2005), implying that, in contrast to acyl ghrelin, des-acyl ghrelin generates a negative energy balance (Asakawa et al, 2005).…”
Section: Normal Physiology Of Des-acyl Ghrelin and Regulation Ofmentioning
confidence: 99%
“…At first, des-acyl ghrelin was regarded as a nonfunctional ghrelin ligand. Desacyl ghrelin has been shown to actively participate in food intake (Asakawa et al, 2005;Chen et al, 2005a,b;Matsuda et al, 2006;Toshinai et al, 2006;Muscaritoli et al, 2007;Inhoff et al, 2008;Stengel et al, 2008), gut motility (Asakawa et al, 2005;Chen et al, 2005a,b), body size development Asakawa et al, 2005), adipogenesis (Thompson et al, 2004), insulin secretion and resistance (Broglio et al, 2004b;Gauna et al, 2004Gauna et al, , 2005Gauna et al, , 2007Iwakura et al, 2005;Qader et al, 2008;Zhang et al, 2008b;Kiewiet et al, 2009), to increase tension of guinea pig papillary muscle ex vivo (Bedendi et al, 2003), and cell proliferation and survival in vitro (Baldanzi et al, 2002;Cassoni et al, 2004Cassoni et al, , 2006Granata et al, 2006Granata et al, , 2007Filigheddu et al, 2007). A more recent study revealed that des-acyl ghrelin was secreted in a highly regulated manner in response to food deprivation in mice (Kirchner et al, 2009).…”
Section: Ghrelin Gene Products In Food Intake and Gut Motilitymentioning
confidence: 99%